Biomimetic catalysis - Breslow, Ronald (Henry Stewart Talks, 2008)
Biomimetic catalysis, Imitating enzymes for improved chemistry, Using geometric control in a catalyst-substrate complex, Mimics of cytochrome P-450, and of transaminase enzymes, High rate accelerations and high selectivities